The Role of Productive Zakat in Improving MSME Performance: A Quantitative Study of Mustahik Assisted by Zakat Institutions in West Java - Sumaryanto, Purwidi; Muhtadi, Muhamad Ammar; Lesmana, Tera (Westscience Press, 2025)
This study investigates the role of productive zakat in improving the performance of Micro, Small, and Medium Enterprises (MSMEs) assisted by zakat institutions in West Java. Productive zakat, as a form of Islamic social finance, aims to empower mustahik (zakat recipients) by providing business capital, training, and guidance to foster economic independence and sustainability. Using a quantitative approach, data were collected from 100 MSME zakat recipients through structured questionnaires based on a five-point Likert scale. Data analysis was conducted using SPSS version 25, including validity, reliability, classical assumption, and multiple regression tests. The results reveal that productive zakat utilization, entrepreneurial capacity, and institutional support each have a positive and significant effect on MSME performance. The coefficient of determination (R²) value of 0.673 indicates that 67.3% of MSME performance variation is explained by these three variables. The findings underscore the crucial role of effective zakat management and capacity-building initiatives in achieving sustainable empowerment. This study contributes to the understanding of how Islamic social finance instruments, particularly productive zakat, can serve as a catalyst for inclusive economic development and poverty reduction in Indonesia.